AN ANALYSIS OF SOCIOLOGICAL PERSPECTIVES ON ILLEGAL MIGRATION OF HARYANA YOUTH TO EUROPE AND AMERICA - Anil; Joginder; Malik, Naveen; Singh, Kulvir (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The main objective of the research paper is to discuss the causes and effects of illegal migration from India. Illegal migration is a complex process, which is being seen all over the world. According to sociological studies, the number of migrant unemployed workers has started increasing towards international migration. The present research is based on the theoretical method of R. K. Merton. R. K. Merton proposed his theory of anomie. In which he stated that any society has important cultural goals, which provide a framework of aspirational reference. When a person has internally accepted a goal, and legitimate means of achieving that goal are blocked, then the person resorts to illegitimate means to achieve the goal, then it is an innovation method. Especially at the international level, in the UK and the United States, the migrant population lives in marginal areas. And this illegal migrant is a threat to health, employment, education and environment. The main reasons giving rise to illegal migration are persecution, war, employment opportunities, higher income, better facilities. It is important to do this type of study to understand migration and overcome the problems related to it. Because illegal migration has become a problem.